Does total playing time affect the neuromuscular, physiological, and subjective recovery of futsal players during a congested period? - Spyrou, K.; Armendáriz, M. L. P.; Alcaraz, P. E.; Carrasco, R. H.; Udayanga, M. A. S.; Freitas, T. T. (Sports, 2024)
The aims of this study were to analyze the effects of a congested period (three games in four days) on countermovement (CMJ) jump-landing metrics, heart rate variability (HRV), and total recovery quality (TQR) score in under-19 male futsal players, and to detect the differences between those who played for more minutes (HIGHMIN) and less minutes (LOWMIN). Fourteen youth futsal players (age: 17.5 ± 0.5 years; body mass: 70.2 ± 8.5 kg; height: 1.80 ± 0.1 m) participated. HRV, TQR questionnaire, and CMJ metrics (i.e., CMJ height, relative peak power (PPREL), eccentric and concentric impulse, braking time, and time to peak force) were registered. A linear mixed model and effect sizes (ESs) were used to assess the differences between groups and days. Considering the total sample, a significant decrease was found in the PPREL and TQR score (p = 0.001-0.013 and ES = 0.28-0.99) on Days 2, 3, and 4 when compared to Day 1. HIGHMIN group presented a significant decrease in PPREL on Day 3 (p = 0.004; ES: 0.62; 95% CI: 0.39-2.65) when compared to Day 1, and in the TRQ score on Day 3 (p = 0.002; ES: 1.98; 95% CI: 0.18-2.46) and 4 (p = 0.003; ES: 2.25; 95% CI: 0.52-3.38) when compared to Day 1. Non-significant differences were found for the rest of the metrics and in the group LOWMIN. In summary, neuromuscular performance (i.e., CMJ PPREL) and subjective recovery were impaired in players with higher playing minutes during a match-congested period when compared to those with less on-court time.